Efektifitas Pembentukan Kampung KB sebagai Indikator Perubahan Perilaku Masyarakat di Jl. Muharto Gang 5B RW 08 Kelurahan Kotalama Malang: Effectiveness of the Establishment of the KB Village as an Indicator of Community Behavior Change on Jl. Muharto Gang 5B Rw 08 Kelurahan Kotalama Malang (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
KB Village is one of the KKBPK strengthening programs that is managed and managed from, by and for the community to empower and provide facilities for the community. This study aims to look at the relationship between the community and the existence of KB villages. Quantitative research methods with cross sectional methods. The data collection tool consisted of a questionnaire with a sample of 100 respondents. This research uses purposive sampling technique. Statistical tests using chi-square and fisher precisely in the univariate and bivariate analysis. The results of the study found that the effectiveness of the KB respondents' village formation was moderate (50%), the respondent's behavior (62%) was sufficient and the Spearman trial results obtained sig. (2-tailed) of 0.00 so ? <0.01 (?) there is a relationship between the effectiveness of the formation of the KB village with changes in society. KB Village on Jl. Muharto Gang 5B Rw 08 Kotalama Malang needs great appreciation and support from various needs that have been managed, so that it becomes an indicator of the KB village process that began in 2017 and ends in 2019 that can be adjusted to the needs of the community better.